2003
DOI: 10.1007/s00122-003-1491-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution genetic mapping of Xa27(t), a new bacterial blight resistance gene in rice, Oryza sativa L.

Abstract: Bacterial blight of rice, caused by Xanthomonas oryzae pv. oryzae ( Xoo) (Ishyama) Dye, is one of the serious diseases prevalent throughout Asia. In a previous study, a resistance ( R) locus was transferred from the tetraploid wild rice Oryza minuta to the cultivated rice species, Oryza sativa L. Here, we report the fine genetic mapping of the R locus, tentatively designated as Xa27(t). We performed disease evaluation with an Xa27(t) near-isogenic line, IRBB27, testing 35 Xoo strains collected from 11 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 29 publications
2
95
2
3
Order By: Relevance
“…This illustrates the utility of comparative genome mapping for map-based cloning of agronomically important genes. Gu et al (2004) also found a good syntenic relationship between the genetic map of the Xa27(t) region in the rice line IRBB27 and in O. sativa cv. Nipponbare.…”
Section: Discussionmentioning
confidence: 75%
“…This illustrates the utility of comparative genome mapping for map-based cloning of agronomically important genes. Gu et al (2004) also found a good syntenic relationship between the genetic map of the Xa27(t) region in the rice line IRBB27 and in O. sativa cv. Nipponbare.…”
Section: Discussionmentioning
confidence: 75%
“…The locations of three characterized rice NBS-LRR resistance genes, Pib, Pita, and Xa1, are designated with arrows. The approximate map positions of other bacterial blight (designated Xa-) and blast (designated Pi-) resistance genes that have been mapped by phenotype by various groups Causse et al 1994;Conaway-Bormans et al 2003;Gu et al 2004;Jeon et al 2003;Jiang and Wang 2002;Li et al 1999;Liu et al 2002;Porter et al 2003;Sallaud et al 2003;Tabien et al 2002;Wang et al 1994;Yoshimura et al 1995) are shown to the right of the chromosomes NBS portions of their coding regions were compared, even between group members that were duplicated on different chromosomes. Many groups have members mapping to different chromosomes that have as little as 30% amino acid sequence identity (Table 2).…”
Section: Genome Organization Of Rice Nbs-lrr Genesmentioning
confidence: 99%
“…Secondly, RCA enables to confirm the candidate markers for mapping the target gene on its chromosome using the homo-recessive progenies (Pan et al 2003;Zhu et al 2004a). Third, BIA allows us to adopt and/or develop molecular markers in the target region, and to construct a physical map spanning the target gene locus, in silico (Gu et al 2004;Chen et al 2005;Liu et al 2005). As a result, the bph19(t) locus was genetically defined to a chromosomal interval of 1.0 cM in length with five cosegregated markers, and physically mapped to a DNA fragment of 60-kb in length.…”
Section: Discussionmentioning
confidence: 99%
“…1, and also see subsequently). The recombination frequency between a marker and the resistance gene was calculated using the following formula: c = N r /2N, in which N is the total number of the resistant individuals tested, N r is the number of recombination events occurred at the respective locus (Pan et al 2003;Gu et al 2004). The recombination frequency was transformed into centimorgans according to the Kosambi function (Kosambi 1944).…”
Section: Evaluation Of the Bph Resistancementioning
confidence: 99%
See 1 more Smart Citation